HUBUNGAN KETERAMPILAN MEMAHAMI TEKS CERITA PENDEK DENGAN KETERAMPILAN MENULIS TEKS CERITA PENDEK SISWA KELAS XI SMA SEMEN PADANG - Andria Catri Thamsin, Mira Handriyani, Harris Effendi Thahar, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
This research is aimed to describe following three aspects. First, describing the level of skills to understanding the text of short stories of Semen Padang Senior High School grade XI Students. Second, describing the level of skill of writing short story text of Semen Padang Senior High School grade XI Students. Third, describe the relationship between the skills to understand short story text and the skills to write short story text of Semen Padang Senior High School grade XI Students. Based on the results of data analysis concluded the following three points. First, the skill to understand short story text of Semen Padang Senior High School grade XI Students is in Good qualification (B) with average count 78.03. Second, the skill of writing short story text of Semen Padang Senior High School grade XI Students is in Good qualification (B) with average count 79,12. Third, based on t-test results, alternative hypothesis (H1) is accepted at 95% confidence level and derajat kebebasanÂ  (dk) = n-1 because thitungÂ  > ttabel (8,81 > 1,70).Kata Kunci : hubungan, keterampilan, memahami, menulis, tes cerita pendek.